[PP.10.14] THE EFFECT OF RENAL DENERVATION IN MODERATE TREATMENT RESISTANT HYPERTENSION WITH CONFIRMED MEDICATION ADHERENCE. (September 2016) - Ott, C.; Mahfoud, F.; Schmid, A.; Ewen, S.; Toennes, S.W.; Meyer, M.R.; Helfer, A.G.; Maurer, H.H.; Ditting, T.; Veelken, R.; Zivanovic, I.; Uder, M.; et al.
Abstract : Objective: Data on the blood pressure (BP) lowering effect of renal denervation (RDN) in moderate treatment resistant hypertension (TRH) are limited. Moreover, change of adherence to medication, as one potential confounder of BP response, has never been analyzed rigorously in this group of patients. We analyzed the effect of RDN on BP in patients with moderate TRH who were retrospectively found to be completely adherent to their antihypertensive medication. Design and method: Our study cohort comprised 40 patients with moderate TRH (office BP > = 140/90mmHg, but <160/100mmHg and 24-h ambulatory BP monitoring [ABPM] > = 130/80 mmHg), who underwent catheter-based RDN. Further major inclusion criterion was complete adherence to their medication (> = 80% intake of their prescribed antihypertensive drugs) at baseline (assessed by retrospective toxicological analysis). Results: Six months after RDN office BP was reduced by −10/−6 mmHg (systolic: 149 ± 6 mmHg vs. 139 ± 15 mmHg; diastolic: 81 ± 12 mmHg vs. 75 ± 10 mmHg; both p < 0.001) and 24-h ABPM by −7/−4 mmHg (systolic: 150 ± 14 mmHg vs. 143 ± 16 mmHg, p = 0.005; diastolic: 82 ± 10 mmHg vs. 78 ± 9 mmHg; p = 0.009). Number of prescribed antihypertensive medication (6.0 [5.0 – 6.0] vs. 5.5 [5.0 – 6.0], p = 0.013) and adherence rate (95.2 ± 7.6 % vs. 91.7 ± 13.9 %, p = 0.065) was slightly reduced 6 months after RDN, both likely to underestimate the true BP reduction. Conclusions: Thus, our data indicate that even after given full respect to drug adherence as potential confounder of BP response after RDN both office and 24-h ABPM were substantially reduced in patients with moderate TRH.